Traffic-related air toxics and Parkinson's disease in California's Central Valley - Dayoon Kwon; Kanghong Shao; Karl O'Sharkey; Yu Yu; Jason Su; Jeff M. Bronstein; Beate Ritz (Science of The Total Environment, 2026)

Characterizing the relationship between air pollution and childhood cognition in the Children's health and air pollution study - Sierra Loomis; Liza Lutzker; Mikaela Holland; Tim Tyner; S. Katharine Hammond; John Balmes; Jason Su; Elizabeth Noth; Stephanie Holm (Environmental Research, 2026)

Association of prenatal exposure to criteria air pollutants and traffic-related air toxics with adverse birth outcomes: A population-based cohort study in California (1990–2021) - Sanjali Mitra; Karl O'Sharkey; Seung-a Paik; Laura Thompson; Jason Su; Myles Cockburn; Roch A. Nianogo; Beate Ritz (Environmental Research, 2026)

Multiscale hierarchically wrinkled MoS2 nanosheet films with enhanced photoelectrochemical properties - Su Yeon Jung; Dong Su Kim; Dongjoon Rhee; Kun Woong Lee; Yun Seong Cho; Adam D. Alfieri; Jason Lynch; Deep Jariwala; Hyung Koun Cho; Joohoon Kang (Chemical Engineering Journal, 2026)

The relationship between all-cause mortality and air pollution: a systematic review focusing on vulnerable populations - Eliana E. Kim; Jasmine Kang; Jason Su; Sei J. Lee (Air Quality, Atmosphere & Health, 2026)
Introduction. Ambient air pollution is known to cause premature deaths worldwide, but gaps remain in understanding its impact on life expectancy across different vulnerable populations. Our objective was to conduct a systematic review of the association of long-term exposure to PM2.5, ozone, and nitrogen dioxide (NO2) on all-cause mortality, with a focus on vulnerable populations. Methods. We searched PubMed, MEDLINE, and Web of Science from January 1, 2000 to October 19, 2023 for studies examining the impact of air pollution on life expectancy or mortality. Two reviewers independently screened 3,764 abstracts and assessed 192 full-text articles. Studies were included if they examined long-term exposure (≥ 1 year) to ambient PM2.5, ozone, or NO2, and reported all-cause mortality. Risk of bias was evaluated using the ROBINS-E tool. Effect estimates for all-cause mortality and subgroup analyses focusing on vulnerable populations (older adults, historically minoritized racial groups, those with comorbidities or low socioeconomic status) were extracted. Results. Thirty-nine studies published from 2000 to 2023 were included. Most studies originated from North America (n = 22) and Europe (n = 9). Study size ranged from 2,734 to 73.4 million participants. Across studies, long-term exposure to PM2.5, ozone, and NO2was consistently associated with increased all-cause mortality, with a trend toward stronger associations among vulnerable populations including individuals with pre-existing health conditions, lower socioeconomic status, and urban residence. The highest mortality burden from air pollution was observed on Black Americans and adults aged 65–74. Conclusion. Long-term exposure to air pollution increases all-cause mortality and appears to disproportionately affect vulnerable populations.

Comparison of surface-guided radiotherapy-based deep inspiration breath hold and continuous positive airway pressure techniques in left-sided breast cancer: dosimetric and workflow analysis - Su Chul Han; Jason Joon Bock Lee; Jin Dong Cho; Il Sun Jeong; Heerim Nam; Hyebin Lee (Physical and Engineering Sciences in Medicine, 2026)

Spatial and temporal effects of Eurosta solidaginis-induced stem galls on leaf physiology in Solidago canadensis - Michelle J. Chin; Mari Alkassam; Mannat Bagga; Su Hyun Elizabeth Ko; Jason C. L. Brown (Arthropod-Plant Interactions, 2026)

Air toxics and late-life dementia and cognitive impairment in Mexican Americans - Yu Yu; Jason Su; Sanjali Mitra; Yufan Gong; Shiwen Li; Yuyuan Lin; Karl O'Sharkey; Kimberly C. Paul; Beate Ritz (Environmental Research, 2025)

Corrigendum to ‘Deciphering the toxicity of polyhexamethylene guanidine phosphate in lung carcinogenesis: Mutational profiles and molecular mechanisms’ [Chemosphere Volume 368 (2024) 143785] - Hong Lee; Sang Hoon Jeong; Yong-Wook Baek; Hyejin Lee; Jason K. Sa; Ji Yoon Lee; Yu-Seon Lee; Yoon Jeong Nam; Jaeyoung Kim; Jonghoon Kim; Jin Young Choi; Su A. Park; et al. (Chemosphere, 2025)

Deciphering the toxicity of polyhexamethylene guanidine phosphate in lung carcinogenesis: Mutational profiles and molecular mechanisms - Hong Lee; Sang Hoon Jeong; Yong-Wook Baek; Hyejin Lee; Jason K. Sa; Ji Yoon Lee; Yu-Seon Lee; Yoon Jeong Nam; Jaeyoung Kim; Jonghoon Kim; Jin Young Choi; Su A. Park; et al. (Chemosphere, 2024)

Neighborhood greenness and participation in specific types of recreational physical activities in the Sister Study - Laura A. Rodriguez-Villamizar; Kim Hellemans; Michael Jerrett; Jason Su; Dale P. Sandler; Paul J. Villeneuve (Environmental Research, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

Air pollution and the sequelae of COVID-19 patients: A multistate analysis - Michael Jerrett; Claudia L. Nau; Deborah R. Young; Rebecca K. Butler; Christina M. Batteate; Ariadna Padilla; Sara Y. Tartof; Jason Su; Richard T. Burnett; Michael J. Kleeman (Environmental Research, 2023)

Enabling Efficient Design of Biological Formulations through Advanced Characterizations - Kang Chen; Jason K. Cheung; Hai-Young Kim; Anthony Leone; Krishna Mallela; Yongchao Su (Pharmaceutical Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Location-weighted traffic-related air pollution and asthma symptoms in urban adolescents - Anne Mielnik; Sheena E. Martenies; Judy M. Heiderscheidt; Jason Su; Zev Ross; Michael Jerrett; John R. Balmes; Sheryl Magzamen (Air Quality, Atmosphere & Health, 2022)

Remodeling of Arctic char ( Salvelinus alpinus ) lipidome under a stimulated scenario of Arctic warming - Chao Wang; Yufeng Gong; Fuchang Deng; Enmin Ding; Jie Tang; Garry Codling; Jonathan K. Challis; Derek Green; Jing Wang; Qiliang Chen; Yuwei Xie; Shu Su; et al. (Global Change Biology, 2021)
Arctic warming associated with global climate change poses a significant threat to populations of wildlife in the Arctic. Since lipids play a vital role in adaptation of organisms to variations in temperature, high‐resolution mass‐spectrometry‐based lipidomics can provide insights into adaptive responses of organisms to a warmer environment in the Arctic and help to illustrate potential novel roles of lipids in the process of thermal adaption. In this study, we studied an ecologically and economically important species—Arctic char ( Salvelinus alpinus )—with a detailed multi‐tissue analysis of the lipidome in response to chronic shifts in temperature using a validated lipidomics workflow. In addition, dynamic alterations in the hepatic lipidome during the time course of shifts in temperature were also characterized. Our results showed that early life stages of Arctic char were more susceptible to variations in temperature. One‐year‐old Arctic char responded to chronic increases in temperature with coordinated regulation of lipids, including headgroup‐specific remodeling of acyl chains in glycerophospholipids (GP) and extensive alterations in composition of lipids in membranes, such as less lyso‐GPs, and more ether‐GPs and sphingomyelin. Glycerolipids (e.g., triacylglycerol, TG) also participated in adaptive responses of the lipidome of Arctic char. Eight‐week‐old Arctic char exhibited rapid adaptive alterations of the hepatic lipidome to stepwise decreases in temperature while showing blunted responses to gradual increases in temperature, implying an inability to adapt rapidly to warmer environments. Three common phosphatidylethanolamines (PEs) (PE 36:6|PE 16:1_20:5, PE 38:7|PE 16:1_22:6, and PE 40:7|PE 18:1_22:6) were finally identified as candidate lipid biomarkers for temperature shifts via machine learning approach. Overall, this work provides additional information to a better understanding of underlying regulatory mechanisms of the lipidome of Arctic organisms in the face of near‐future warming.

Identification of major insect pests of Amaranthus spp. and germplasm screening for insect resistance in Tanzania - Jason D. Smith; Fekadu F. Dinssa; Robert S. Anderson; Fu-cheng Su; Ramasamy Srinivasan (International Journal of Tropical Insect Science, 2018)

Multi-pollutant Modeling Through Examination of Susceptible Subpopulations Using Profile Regression - Eric Coker; Silvia Liverani; Jason G. Su; John Molitor (Current Environmental Health Reports, 2018)

A quantitative assessment of precipitation associated with the ITCZ in the CMIP5 GCM simulations - Ryan E. Stanfield; Jonathan H. Jiang; Xiquan Dong; Baike Xi; Hui Su; Leo Donner; Leon Rotstayn; Tongwen Wu; Jason Cole; Eiki Shindo (Climate Dynamics, 2016)

Reconstructing Agriculture in Vitcos Inca Settlement, Peru - Enrique Meseth; Liang‐Chi Wang; Su‐Hwa Chen; Jason C. S. Yu; Michael Buzinny (Irrigation and Drainage, 2015)
Vitcos was occupied by the Incas of Vilcabamba in the sixteenth century, which included about 20 ha of agricultural fields with crops such as maize, potato, quinoa, amaranth and beans. The current study assessed water management for agriculture on this site. Desk research included relating past climatic data to a parallel study on modern climate, evapotranspiration, crop schedules, crop water requirements and capillary rise estimates; additionally, field studies comprised soil sample collection and analysis, watercourse flow measurements and hydrological interpretation, GIS mapping of crop fields, and the reconstruction of crops with palynology techniques and radiocarbon dating. Results indicate that irrigation requirements for crops sown once a year occurred only in May, for potato (15.3 mm) and quinoa (3.5 mm), but rainfed irrigation was feasible if capillary rise is considered. Finally, the Inca population of Vitcos was estimated in relation to food production, considering dietary habits, crop field area, crop yields, nutrition value of crops and calorie requirements, reaching 365 people, taking into account that crops were sown once a year and meat supply represented 10% of the diet. This estimate matches with the number of people that could have been accommodated in Vitcos Inca dwellings. Copyright © 2015 John Wiley & Sons, Ltd.

The Influence of Recrystallized Caffeine on Water-Swellable Polymethacrylate Mucoadhesive Buccal Films - Javier O. Morales; Rong Su; Jason T. McConville (AAPS PharmSciTech, 2013)

Spatial modeling of residential woodsmoke across a non-urban upstate New York region - Jason G. Su; George Allen; Paul J. Miller; Michael Brauer (Air Quality, Atmosphere & Health, 2013)

Mechanisms of toxicity of triphenyltin chloride (TPTC) determined by a live cell reporter array - Guanyong Su; Xiaowei Zhang; Jason C. Raine; Liqun Xing; Eric Higley; Markus Hecker; John P. Giesy; Hongxia Yu (Environmental Science and Pollution Research, 2013)

MRI Blood–Brain Barrier Permeability Measurements to Predict Hemorrhagic Transformation in a Rat Model of Ischemic Stroke - Angelika Hoffmann; Jörg Bredno; Michael F. Wendland; Nikita Derugin; Jason Hom; Tibor Schuster; Claus Zimmer; Hua Su; Peter T. Ohara; William L. Young; Max Wintermark (Translational Stroke Research, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)